Role of Government and Non-Government Organizations in Boosting Agricultural Production towards Meeting Household Nutrition as Perceived by Rural Women - Kawsher Ahmed; M Zulfikar Rahman; M Golam Farouque; M Asaduzzaman Sarker; Md. Rayhan Sojib (Journal of Extension Education, 2023)
The study was undertaken to have an understanding of rural women’s perception of the role played by the government and non-government organizations (GOs and NGOs) to boost agricultural production in Lama upazila under Bandarban district of Bangladesh towards meeting household nutrition. Besides, attempts were made to explore the quality of service provided by the GOs and NGOs to boost agricultural production and to explore the problems faced by them to meet the demand of household nutrition. Eighty six percent of rural women perceived the role played by the GOs and NGOs as ’somehow satisfied’ to ’satisfied level’. Among the rural women, 90 percent of the respondents expressed that they face moderate to high level of problems to meet their demands for household nutrition. The services from the all concerned GOs and NGOs should be provided in such a way that could help more to boost agricultural production as well as meet the demand of household nutrition of the rural women in the study area.